The Role of Fire Detection Equipment To Prevent Fires In MV. Soemantri Brodjonegoro - Ilham, Chairul Insani; Katharina, Santy; Panggabean, Yunita (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2023)
The role of fire detection tools is very helpful in preventing fire hazards in MV. Soemantri Brodjonegoro, on this basis, the author formulates the problem of the extent of the ship's crew's knowledge of fire detection tools and how to maintain fire detection tools in MV. Soemantri Brodjonegoro. The method used in this study is a qualitative method that produces descriptive data in the form of written words from people and observed behaviors. In this case, collecting data in the form of an approach to the object through observation, direct interviews with the subject. Based on the results of research and discussion of problems carried out by the author during the practice of screening in MV. Soemantri Brodjonegoro regarding the role of fire detection devices found problems in the role of fire detection devices which include the lack of knowledge of ship crews about fire detection tools caused by the lack of implementation of new crew familiarization and the lack of implementation of safety meetings on ships. The discussion of the results of the study is to increase the ship crew's knowledge of fire detection equipment by means of maximum familiarization of the new crew and carry out safety meetings once a month, as well as improve the maintenance of fire detection equipment by means of good coordination between the ship and the company and increasing the responsibility of ship officers by checking fire detection equipment regularly. In this case, it is concluded that the lack of knowledge of the ship's crew and the maintenance of fire detection equipment can cause the malfunction of the tool properly, namely as a tool to detect fire hazards on board so that the fire detection tool can function properly to support shipping.